2010
DOI: 10.1111/j.1399-5618.2010.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem in remitted bipolar disorder patients: a meta‐analysis

Abstract: By revealing that BD patients do experience low self-esteem, the findings implicate a need for further understanding the causes and therapeutic impact of such abnormality in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 65 publications
(66 reference statements)
1
35
0
2
Order By: Relevance
“…[33][34][35][36][37] Moreover, there is com- provided as an 8-session intervention 8-session intervention MBSR = mindfulness-based stress reduction, MBCT = mindfulness-based cognitive therapy pelling evidence that processing of self-referent information is abnormal in affective illness. [38][39][40][41] Other research also suggests that an association exists between self-esteem and mood and anxiety disorders, including bipolar disorder, 39,42 generalized anxiety disorder, 43 obsessive-compulsive disorder, 44,45 PTSD, 46-48 social phobia, 49,50 and panic disorder. 51 Finally, the effectiveness of interventions targeting negative schemas through cognitive therapy for the treatment of mood disorders is well established.…”
Section: Psychological Mechanismsmentioning
confidence: 95%
“…[33][34][35][36][37] Moreover, there is com- provided as an 8-session intervention 8-session intervention MBSR = mindfulness-based stress reduction, MBCT = mindfulness-based cognitive therapy pelling evidence that processing of self-referent information is abnormal in affective illness. [38][39][40][41] Other research also suggests that an association exists between self-esteem and mood and anxiety disorders, including bipolar disorder, 39,42 generalized anxiety disorder, 43 obsessive-compulsive disorder, 44,45 PTSD, 46-48 social phobia, 49,50 and panic disorder. 51 Finally, the effectiveness of interventions targeting negative schemas through cognitive therapy for the treatment of mood disorders is well established.…”
Section: Psychological Mechanismsmentioning
confidence: 95%
“…A meta-analysis of data from 12 trials (n = 1838) found that the self-esteem of patients with remitted BD was significantly lower than that of controls but significantly higher than that of patients with remitted major depressive disorder (MDD) (12). In addition, self-esteem may follow a fluctuating course during remission of BD.…”
Section: Impactmentioning
confidence: 99%
“…BD is associated with a greatly impaired quality of life, increased physical health burden (Vancampfort et al, 2016;Vancampfort et al, 2015) and disability (Hirschfeld et al, 2003;Yatham et al, 2004). Moreover, BD can impact employment (Reed et al, 2010) and lead to lower self-esteem (Nilsson et al, 2010) and reduced social interaction (Judd and Akiskal, 2003). Furthermore, approximately 23% of patients with BD report a history of suicide attempts (Kattimani et al, 2016) BD has a complicated, multifactorial etiology including genetic, neuro-endocrine, and environmental factors (Craddock and Sklar, 2013).…”
Section: Introductionmentioning
confidence: 99%